PRODUCT DEVELOPMENT STRATEGY FOR ESSENTIAL OIL MADE FROM JASMINE, CANANGA FLOWERS, AND ROSES IN BANJAR REGENCY OF SOUTH KALIMANTAN - Heri Soedarmanto; Rabiatul Adawiyah; Nur Diana; Evy Setiaati; Yuniati Yuniati; Fauzia Ayu Nurhany (UJoST- Universal Journal of Science and Technology, 2023)
Some residents of Banjar Regency, South Kalimantan Province, Indonesia depend on ornamental plants as their livelihoods; they plant jasmine (Jasminum sambac), roses (Rosa spp.), and Cananga (Cananga odorata). Each flower produces a distinct scent. Floral scents are commonly used as aromatherapy because the scent is calming and relaxing. Some floral scents even can bring a healing effect. Floral scents are composed of all the volatile organic compounds (VOCs), or aroma compounds, emitted by floral tissue (for example, flower petals), commonly referred to as floral essential oil. Floral essential oil has complex chemical compounds. This study analyzes the product development strategy for essential oil made from jasmine, Cananga, and roses in Banjar Regency, South Kalimantan Province, Indonesia. We had four villages as the study sites, namely Jingah Habang Ilir, Jingah Habang Ulu, Pandak Daun, and Loktangga. Data were collected through observations, interviews, documentation, recording, and Focus Group Discussion (FGD). The product development strategy covers many aspects: market-segment strategy, price strategy, market potential strategy, and market growth strategy.